Thinking from Within A Hands-On Strategy Practice - Roos, J. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2006)
This text is a tribute to the idea that strategy should be practised in ways that fuel our minds by engaging our bodies. When we do strategy rather than think strategy we engage our senses in ways that pure intellectual reasoning cannot. This book considers ideas that can help leaders transform strategy into imaginative and responsible practice.